Professionalism Criteria in the Egyptian Civil Service System: An Analytical Study - Nasreldeen, Sarah (The Arab Journal of Administration, 2025)
Professionalism means that a field or an occupation has the same characteristics of a traditional profession like medicine, engineering, and law. The aim of this paper is to scrutinize five main criteria of professionalism in the Egyptian civil service system (ECSS), specifically public administration (PA) positions (e.g., managers, human resources officers, etc.). These criteria include: the academic background required to hold a job related to the PA field, professional licensing, training, codes of ethics, and self-regulation (associations or syndicates). The paper sought to contribute in filling the gap in the literature regarding examining comprehensive criteria of professionalism in the Egyptian case and it ended up with a number of recommendations for the policy-maker. This study depended on a qualitative analytical methodology through scrutinizing seven successive laws of the civil service in Egypt with regard to the professionalism standards, besides some secondary data. The research concluded that professionalism criteria were developing in ECSS across time. It has partially fulfilled numerous criteria of professionalism in PA entailed providing the opportunity by the law to require a specialized academic qualification to fill a specific job, licensing through examination, and having codes of ethics. However, it still needs to boost other standards to be fully professionalized, such as establishing a regulatory body for PA occupations and an accredited training school. It found that the legal framework is flexible; thus, the internal executive regulation of each public entity can be easily reformed to satisfy professionalism criteria in the recruiting process. Hence, the legal framework is not a hurdle to professionalism in civil service, despite some of the shortcomings.